Levels of anxiety, depression and stress among health care workers during the COVID19 pandemic: Study conducted at the University Hospital Farhat Hached of Sousse-Tunisia - Belhadj Chabbah, N.; Chatti, S.; Athimni, Z.; Bouhoula, M.; Chouchane, A.; Aloui, A.; Kacem, I.; Maoua, M.; Brahem, A.; Kalboussi, H.; Elmaalel, O.; Mrizek, N. (European psychiatry, 2023)
IntroductionDuring the COVID-19 pandemic, health care workers found themselves threatened by developing psychological effects.ObjectivesThe objective of this study is to evaluate the impact of exposure to COVID-19 on the mental health of medical and paramedical staff at Farhat Hached Hospital in Sousse and to identify potential risk factors.MethodsThis is a descriptive cross-sectional study that included 166 health care workers of Farhat Hached Hospital of Sousse throughout 3 months. The patient health questionnaire (PHQ-9), the generalized anxiety disorder (GAD-7), and the revised event impact scale (IES- R) were used to assess depression, anxiety, and stress respectively.ResultsThe mean age of the participants was 37.06 ±11.07 years with a female predominance (80.1%). The median professional seniority was 7.5 years with extremes ranging from 1 to 39 years. Nurses were the most represented (34.3%) followed by medical residents (24.7%). PHQ-9, GAD-7, and IES- R scores revealed that 51.8%, 40.4%, and 28.3% of participants had moderate or severe levels of depression, anxiety, and stress, respectively. Personal history of psychiatric disorders was significantly associated with depression (p<10-3) and anxiety (p=0.004). On the other hand, paramedical staff had a significantly higher risk of experiencing symptoms of depression (OR = 2.40 ; 95% CI [1.28-4.48] ; p= 0.006) and stress (OR = 2.03 ; 95% CI [1.01-4.11] ; p= 0.04) than medical personnel.ConclusionsThis study reported a high prevalence of symptoms of anxiety, depression and stress among health care workers. Improving mental well-being and providing psychological support to health care workers is recommended.Disclosure of InterestNone Declared